2022
DOI: 10.1172/jci.insight.160308
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific differences in NPC1 protein trafficking govern therapeutic response in Niemann-Pick type C disease

Abstract: The folding and trafficking of transmembrane glycoproteins are essential for cellular homeostasis and compromised in many diseases. In Niemann-Pick type C disease, a lysosomal disorder characterized by impaired intracellular cholesterol trafficking, the transmembrane glycoprotein NPC1 misfolds due to disease-causing missense mutations. While mutant NPC1 has emerged as a robust target for proteostasis modulators, these drug development efforts have been unsuccessful in mouse models. Here, we demonstrate unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…More generally, BET proteins have been shown to control lysosome- and autophagy-related genes in various cell types and disease conditions (Campbell et al, 2018; Gong et al, 2022; Jang et al, 2017; Li et al, 2020; Sakamaki et al, 2017; Segatto et al, 2020; Shen et al, 2020; Sui et al, 2019; Wakita et al, 2020). Other pathways to enhance cellular NPC1 protein levels have been explored in vitro including inhibition of histone deacetylases (Newton et al, 2017; Nunes et al, 2013; Pipalia et al, 2011; Pipalia et al, 2017; Praggastis et al, 2015; Wang et al, 2019), enhanced chaperone activity (Gelsthorpe et al, 2008; Nakasone et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Schultz et al, 2022; Völkner et al, 2022; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and reduced protein degradation (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Nakasone et al, 2014; Zampieri et al, 2012). Similar to what we observed following JQ1 treatment, these manipulations enhanced the presence of NPC1 variants in the endosomal-lysosomal system (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Pipalia et al, 2017; Völkner et al, 2022; Wang et al, 2019; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and decreased the intracellular accumulation of unesterified cholesterol (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Munkacsi et al, 2011; Newton et al, 2017; Ohgane et al, 2013; Pipalia et al, 2011; Pipalia et al, 2021; Pipalia et al, 2017; Praggastis et al, 2015; Völkner et al, 2022; Wang et al, 2019; Wehrmann et al, 2012; Yu et al, 2012; Zampieri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, BET proteins have been shown to control lysosome- and autophagy-related genes in various cell types and disease conditions (Campbell et al, 2018; Gong et al, 2022; Jang et al, 2017; Li et al, 2020; Sakamaki et al, 2017; Segatto et al, 2020; Shen et al, 2020; Sui et al, 2019; Wakita et al, 2020). Other pathways to enhance cellular NPC1 protein levels have been explored in vitro including inhibition of histone deacetylases (Newton et al, 2017; Nunes et al, 2013; Pipalia et al, 2011; Pipalia et al, 2017; Praggastis et al, 2015; Wang et al, 2019), enhanced chaperone activity (Gelsthorpe et al, 2008; Nakasone et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Schultz et al, 2022; Völkner et al, 2022; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and reduced protein degradation (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Nakasone et al, 2014; Zampieri et al, 2012). Similar to what we observed following JQ1 treatment, these manipulations enhanced the presence of NPC1 variants in the endosomal-lysosomal system (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Ohgane et al, 2013; Pipalia et al, 2021; Pipalia et al, 2017; Völkner et al, 2022; Wang et al, 2019; Wang et al, 2020; Yu et al, 2012; Zampieri et al, 2012) and decreased the intracellular accumulation of unesterified cholesterol (Gelsthorpe et al, 2008; Macías-Vidal et al, 2014; Munkacsi et al, 2011; Newton et al, 2017; Ohgane et al, 2013; Pipalia et al, 2011; Pipalia et al, 2021; Pipalia et al, 2017; Praggastis et al, 2015; Völkner et al, 2022; Wang et al, 2019; Wehrmann et al, 2012; Yu et al, 2012; Zampieri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Isogenic WT and I1061T NPC1 iNeuron lines were generated as previously described by the Genome Engineering and iPSC Center at Washington University in St. Louis (St. Louis, MO). 36 iPSCs were cultured and differentiated to neurons as previously described and I1061T NPC1 iNeurons exhibited diminished total NPC1 protein levels and impaired trafficking through the Golgi, as reflected by increased EndoH sensitivity and increased Filipin staining compared to WT-NPC1 iNeurons. 36 Briefly, iPSCs were cultured on GelTrex-coated plates in StemFlex Basal Medium, with media changes every other day.…”
Section: Human Ipsc Cell Linementioning
confidence: 99%
“…36 iPSCs were cultured and differentiated to neurons as previously described and I1061T NPC1 iNeurons exhibited diminished total NPC1 protein levels and impaired trafficking through the Golgi, as reflected by increased EndoH sensitivity and increased Filipin staining compared to WT-NPC1 iNeurons. 36 Briefly, iPSCs were cultured on GelTrex-coated plates in StemFlex Basal Medium, with media changes every other day. For differentiation, iPSCs were dissociated to single cell suspension with Accutase and seeded on GelTrex-coated dishes with StemFlex media supplemented with 10uM Y27632.…”
Section: Human Ipsc Cell Linementioning
confidence: 99%
“…NPC1 passes through the Golgi apparatus and the mature glycans through the action of glycan-modifying enzymes. It becomes resistant to the enzyme endoglycosidase (EndoH), which degrades glycans by cutting [18]. The mature WT NPC1 protein with such post-translational modifications has a half-life of 42 h. In contrast, the WT NPC1 protein without these posttranslational modifications has a half-life of 9 h, and for the NPC1 protein with the I1061T mutation, this time is reduced to only 6.5 h [20].…”
Section: N-glycosylation Implication In Npc1 Functionmentioning
confidence: 99%
“…It has been determined that Nglycosylation of the NPC1 protein confers resistance to EndoH to avoid degradation. This glycosylation process facilitates the transport of the protein from the endoplasmic reticulum (ER) to the late endosomes/lysosomes (LE/Ly) [18]. Additionally, it has been observed that the loss of glycosylation in the N58 chain of the NPC2 protein hinders its transport into lysosomes [19].…”
Section: Introductionmentioning
confidence: 99%